Technical Appraisal of Continuous Destilator Type as Alternative Fuel Producer from Basic Materials of Arak Bali - Sukadana -; Bandem A.; Tenaya - (Jurnal Energi Dan Manufaktur, 2009)
Arrack Bali which is produced from traditional process has low quality (<40%). With controlling of operational variable such as evaporation temperature, will improve arrack Bali quality. Arrack Bali with quality more than 80 % has octane number more than 108,6, higher then petroleum octane number (80 until 90), easy burning and evaporation, very good to be alternative fuel to engine. In order to product height quality any operational variables like temperature, step, and sprayer models should be noticed. This experiment is to obtain operational variables of distillatory to product arrack Bali as an alternative fuel and it is tested in motor cycle engine at speed and compression ratio variables toward performance like emission. The higher evaporation temperature is the higher capacity of product to be obtained, on the other hand, the lower quality to be reached. Generally, comparing with petroleum, arrack Bali yields lower emission.